Authentication of geographic origin and production method of mullet (Mugil cephalus) roe using HRMS-based small-molecule fingerprinting - Yuchieh Tseng; Chia-Hui Wang; Yi-Chieh Lee; Chun-Yu Wang; Keng-Jui Lin; Jia-Zhen Yang; Yutong Chen (Food Control, 2027)

Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Optimal microbial inoculant dosage decouples antibiotic removal from resistance gene attenuation during sludge composting - Dengmiao Cheng; Lizhu Yuan; Jie Chen; Qiuxiang Xu; Hui Lin; Zhen Yu (Bioresource Technology, 2026)

Biomass-derived ceramic packing coupled with an Fe–Mn modified graphite felt cathode for enhanced bioelectro-Fenton/biotrickling filtration of gas-phase styrene - Shu-Hui Liu; Yu-Sheng Yang; Chi-Wen Lin; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Biochar-based cathodes for bioelectro-Fenton systems: Design strategies, electrocatalytic mechanisms, and environmental applications - Shu-Hui Liu; Chung-Yen Yeh; Wei-Tzu Huang; Yi-Chun Yu; Chi-Wen Lin (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Elemental sulfur-enhanced hydrothermal stabilization of arsenic in arsenic sulfide sludges: Mechanism of sulfur-induced structure transformation and practical application - Hui Xu; Wanlan Wu; Qiujing Xu; Yong Ke; Yun Li; Cong Peng; Lin Yu; Zhumei Sun; Yunyan Wang; Xiaobo Min (Journal of Environmental Chemical Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

Enhanced aluminum removal via K+–NH4+ composite alum precipitation from beryllium leachates: Mechanism validation and application - Lin Yu; Xiaobo Min; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Cong Peng; Hui Xu; Zhiyan Zeng; Yong Ke (Hydrometallurgy, 2026)

Regional heterogeneity and vertical stratification of carbon dynamics in Chinese peatlands - Hui Zhang; Minna Väliranta; Angela Gallego-Sala; Zhan-Yi Lin; Chen-Yu Wang; Yan Zhao; Zheng-Tang Guo (Global and Planetary Change, 2026)

Longitudinal associations of per- and polyfluoroalkyl substances with metabolic syndrome from adolescence to early adulthood: A 10-year prospective cohort study - Chien-Yu Lin; Hui-Ling Lee; Ta-Chen Su (Environmental Pollution, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Genome-wide association analysis for resistance against iridovirus disease in large yellow croaker (Larimichthys crocea) from a natural outbreak population - Ying Pan; Hongshu Chi; Nengfeng Lin; Junjia Zeng; Xiaodong Liu; Xiuxia Chen; Zaiyu Zheng; Qiuhuan Jiang; Xunkai Yu; Hui Gong (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Self-powered trickling-filter bioelectro-Fenton removal of gaseous isopropanol using sulfur-modified Fe-biochar fillers and a melanin-modified cathode - Chi-Wen Lin; Yu-Sheng Yang; Shu-Hui Liu; Wei Tong Chen; Xiang-En Ke (Chemical Engineering Journal, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Laboratory investigation on the static and dynamic mechanical behaviors of rubber-sand mixture - Lin Guo; Pinzheng Jiang; Hui Li; Yi Yu; Liguo Liu; Jun Liu (Soil Dynamics and Earthquake Engineering, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Enhanced photocatalytic degradation of cimetidine by using SnS2/TiO2 nanocomposite under simulated solar light - Zi-Jie Guo; Hank Hui-Hsiang Lin; Jheng-Sian Yang; Angela Yu-Chen Lin (Journal of Water Process Engineering, 2026)

Climate change reshapes the dominant drivers of endorheic lakes on the Qinghai-Tibet Plateau - Hui Lin; Xuegao Chen; Nan Xu; Qin Ju; Jingcai Wang; Huanghe Gu; Tongqing Shen; Zhongxiang Wang; Xingrong Si; Jinguo Wang; Zhongbo Yu (Global and Planetary Change, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Breaking boundaries: A social–ecological network approach to collaborative governance of soil erosion risk - Yifan Lin; Jian Peng; Zihan Xu; Tao Hu; Xuebang Liu; Hui Tang; Shuying Yu (Ambio, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Clean heating transition in China: Technological innovation, residual emission burden, and regional inequality in northern cities - Linyan Li; Yunlong Wu; Li Zhang; Huili Wang; Jieyi Li; Lin Xiang; Xiurong Hu; Jiaxuan He; Ling Jin; Xiaojun Chen; Hui Xu; Yu Lei (Sustainable Production and Consumption, 2026)

Exploring antennal asymmetry in electrophysiological response, behavior, and olfactory gene expression in the diamondback moth, Plutella xylostella (lepidoptera: plutellidae) - Houjun Tian; Shuo Lin; Yueqin Zheng; Ruibin Xu; Yun Yu; Yong Chen; Hui Wei (Journal of Insect Physiology, 2026)

Dynamic exposure to per- and polyfluoroalkyl substances and early alterations in cardiovascular hemodynamics: A 10-year longitudinal study in adolescents and young adults - Chien-Yu Lin; Hui-Ling Lee; Ta-Chen Su (International Journal of Hygiene and Environmental Health, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

One-pot biocatalytic synthesis of structurally uniform β-1,3-glucan from renewable cellobiose via a thermostable GH161 phosphorylase in an in vitro biosystem - Guotao Mao; Junhan Lin; Zhe Li; Jin Yu; Ming Song; Miaoqian Wang; Hongsen Zhang; Hui Xie; Zengping Su; Hongge Chen; Andong Song (Food Chemistry, 2026)

Unraveling the effects of selenium and drying on the structure–function relationship of sweet potato protein: A multiscale study - Hui Zhao; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Tao Yu; Xue-Jun Gu; You-Lin Xue (Food Hydrocolloids, 2026)

Long-term increases in urinary metals are associated with lipid peroxidative but not oxidative DNA damage in adolescents and young adults: A 10-year prospective cohort study - Chien-Yu Lin; Po-Chin Huang; Hui-Ling Lee; Ta-Chen Su (Environmental Pollution, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Numerical study of gas-layer drag reduction for a container ship under varied ventilation rate and ship speed conditions - Xiang Lin; Yu Wang; Bo Zhou; Hui Liu; Gaofei Su; Wenqing Luo (Ocean Engineering, 2026)

Multi-source isotopic tracing reveals meltwater runoff processes and environmental responses in the Yarlung Tsangpo River Basin - Zijun Zhang; Xuegao Chen; Hui Lin; Tongqing Shen; Qin Ju; Shiqin Xu; Ningpeng Dong; Peng Yi; Peng Chen; Naifeng Zhang; Yong Huang; Jinguo Wang; et al. (Journal of Hydrology, 2026)

Enhanced hydrolysis-acidification of BTEX-containing cabin-washing wastewater in a continuously operated reactor via iron-carbon composites and flow optimization - Jia-Hui Chen; Yu-Zhu Huang; Tsung-Lin Tsai; Xin-Hua Xu; Li-Hua Cheng (Journal of Environmental Chemical Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Lysosomal dysfunction contributes to lead (Pb) and high-fat diet (HFD)-induced neuronal apoptosis: A link with cathepsin B - Yongke Yuan; Mengchen Liu; Mengdi Zhai; Meijia Wu; Wenhui Zhang; Yongjuan Xin; Yue Ba; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (NeuroToxicology, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular and optical signatures of labile dissolved organic matter during bloom senescence in the Amundsen Sea Polynya - Hui Lin; Qiang Hao; Wei Zhang; Zhenwei Yan; Hao Zhang; Ziming Fang; Yuan Gao; Yong Yu; Ding He (Limnology and Oceanography, 2026)
The Amundsen Sea Polynya (ASP) in the Southern Ocean serves as a potentially significant carbon sink, where phytoplankton blooms drive intense primary production and dissolved organic matter (DOM) cycling. This study focuses on DOM dynamics during the late‐summer bloom phase dominated by Phaeocystis antarctica . Despite the ASP's high productivity, DOM characteristics and their response to bloom senescence remain poorly resolved, limiting insights into carbon sequestration efficiency. We integrated absorbance and fluorescence spectroscopy with Fourier transform ion cyclotron resonance mass spectrometry to analyze seawater samples collected along transects in the ASP during austral summer 2022. Key findings include non‐exponential chromophoric DOM spectra with distinct shoulders at 270–290 nm (aromatic amino acids) and 300–350 nm (mycosporine‐like amino acids), elevated protein‐like fluorescent DOM components linked to P. antarctica degradation, and enrichment of labile, low‐molecular‐weight compounds ( −1 ) amid reduced chlorophyll a (3.81 ± 0.77 mg·m −3 ), indicating DOM release under iron‐replete, nitrate‐limited conditions. This work advances knowledge by identifying unique phytoplankton‐derived DOM signatures that challenge conventional optical metrics like spectral slopes in polar systems, highlighting autochthonous production over terrestrial inputs. Broader implications include improved predictions of carbon cycling in expanding polynyas under climate change, emphasizing reduced sequestration due to labile DOM remineralization and its vulnerability to warming‐induced shifts in Antarctic ecosystems.

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Middle Eocene arc magmatism from Armenia with new insights into tectonic evolution of the Arabia-Eurasia collision zone - Yu-Chin Lin; Kwan-Nang Pang; Ghazar Galoyan; Rafael Melkonyan; Hao-Yang Lee; Ching-Hua Lo; Jin-Hui Yang; Sun-Lin Chung (Lithos, 2026)

Waste lignin-based N/O-rich carbon nanofibers as bifunctional materials for efficient CO2 conversion and energy storage - Wei Hui; Xin Wang; Zao-Lin Hu; Ming-Yu Zhao; Jia-Xin Feng; Wen Chen; Xiao-Yu Xiao; Chuang-Qi Zheng; Lei Pu (Journal of Environmental Chemical Engineering, 2026)

Microbial-assisted copper migration stabilizes Fe/Cu cathodes for long-term bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Yu-Cheng Chiang; Hui Suan Ng; Shu-Hui Liu; Yi-Kai Yang (Journal of Environmental Chemical Engineering, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Sex Differences in Vigilance Functions of Golden Snub-nosed Monkeys (Rhinopithecus roxellana): Females Prioritize Antipredator Vigilance While Males Focus on Social Vigilance - Hui Yu; Chi Zhang; Jinhuang Lin; Ruiyuan Li; Hui Yao; Wanji Yang; Ali Krzton; Yang Yu; Zuofu Xiang (International Journal of Primatology, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Molecular Insights into Exoskeletal Remodeling: Transcriptomic Profiling of the Molting Cycle in the Red Swamp Crayfish Procambarus clarkii - Yunkuan Zhu; Yu Xu; Suwan Lu; Yuning Hu; Hui Xu; Jiajia Li; Hai Lin; Xuguang Li; Zhiqiang Xu (Fishes, 2026)
The molting of crustaceans is accompanied by exoskeleton reconstruction. To reveal the molecular regulation mechanism of exoskeleton remodeling, the transcriptomic profiles of the exoskeleton across the entire molting process in the red swamp crayfish Procambarus clarkii were investigated by RNA sequencing, yielding a total of 7671 differentially expressed genes (DEGs) across five different molting stages. Notably, the key DEGs were those related to cuticular exoskeleton synthesis (cuticular proteins), degradation (chitinase 2, chitinase 10) and hardening (chitin deacetylase 1), and their expression abundance varied by 10-fold or greater across the molting cycle. Analysis of Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that significantly enriched pathways included the structural constituents of the cuticle, structural molecule activity, chitin binding of chitin metabolism, and hormone biosynthesis. The expression profiles of nine selected molting-related DEGs were further validated via real-time RT-PCR assays. The acquired unique temporal expression patterns involved in exoskeleton remodeling provide a preliminary insight into the regulation of gene expression during the molting cycle in the red swamp crayfish.

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Enhancing compost safety: Simultaneous reduction of antibiotic resistance genes and bioavailable heavy metals by microbial additives - Dengmiao Cheng; Yunchang Jiang; Jie Chen; Hui Lin; Zhen Yu (Bioresource Technology, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

Distinction in Symbiodiniaceae and Bacterial Communities and Symbiodiniaceae Lineage‐Specific Transcriptome Underpinning the Superior Heat Tolerance of Intertidal Acropora Corals - Pan Zhang; Lin‐Tao Huang; Xiao‐Lei Yu; Yu‐Yang Zhang; Sheng Liu; Lei Jiang; Hui Huang (Molecular Ecology, 2026)
Fine‐scale thermal heterogeneity within intertidal and subtidal microhabitats could drive divergence in organismal heat tolerance. Reef corals from the extreme intertidal may hold optimism for the future of coral reefs and give insights into the mechanisms by which coral may persist under future conditions. Here, we compared the thermal sensitivities of intertidal and subtidal Acropora digitifera and evaluated their bleaching phenotypes, transcriptomes, host genetic differentiation and bacterial communities. Results showed that only heat‐exposed subtidal corals displayed significantly reduced photochemical efficiency, symbiont densities, pigment and host protein concentrations, suggesting bleaching and host starvation. Despite being genetically similar, heat‐exposed subtidal corals mounted stronger immune activation and amino acid degradation but downregulated monocarboxylate transport and calcification compared to intertidal corals. In contrast to the prevalence of Cladocopium in subtidal corals, intertidal corals were dominated by Durusdinium , whose transcriptional signature was characterised by lineage‐specific and constitutively high transcript abundance of orthologs involved in stress response, metabolism, photosynthesis, cell cycle and symbiotic interactions. Furthermore, 16S rRNA sequencing demonstrated an origin‐dependent bacterial composition, with Endozoicomonas being more abundant and important in co‐occurrence networks of intertidal corals. Our findings suggest that distinction in Symbiodiniaceae and bacterial communities and Symbiodiniaceae lineage‐specific transcriptional footprint largely underpin the exceptional thermotolerance of intertidal Acropora . Although these corals provide promising avenues for restoration, such a mechanism may bring attention to the risk of using them in selective breeding, particularly given the horizontal transmission of algal symbionts in Acropora .

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Rapid degradation of sulfonamide antibiotics and ketamine via combined UV222 and peracetic acid treatment - Min-Qi Cai; Hank Hui-Hsiang Lin; Jheng-Sian Yang; Angela Yu-Chen Lin (Journal of Environmental Chemical Engineering, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Screening of high-risk phytoplankton species and mechanisms of bloom outbreaks in temperate waters adjacent to a nuclear power plant - Youyin Ye; Xiuwu Sun; Heshan Lin; Yu Wang; Yanghang Chen; Qianqian Zhou; Baohong Chen; Xuebao He; Peng Xiang; Hui Lin (Marine Pollution Bulletin, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Dual-Path valorization of organic waste via black soldier fly: Synergistic enhancement of feed efficiency, crop quality, and climate mitigation in closed-loop aquaculture - Longjun Chen; Yu Lin; Xianbo Jia; Xiangzhou Zheng; Yuchen Zhuo; QianQian Chen; Haiping Fan; Yu Fang; Hui Zhang; Chenqiang Lin (Waste Management, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Dual-function microalgal microbial fuel cell for simultaneous wastewater remediation and bioelectricity generation under magnetically stirred cathode configuration - Chi-Wen Lin; Shu-Hui Liu; Yu-Shen Cheng; Baala H. Anandapadmanaban (Journal of Water Process Engineering, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Occurrence of beryllium and its microscale interactions with coexisting phases in beryllium-containing sludge - Xiaobo Min; Lin Yu; Yong Ke; Yunyan Wang; Wenming Zeng; Hui Xu; Yun Li; Cong Peng; Zhumei Sun (Journal of Environmental Sciences, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Evaluating hygroscopic cloud-seeding effects by in-situ observation and real-case simulation - Kai-I Lin; Sheng-Hsiang Wang; Kao-Shen Chung; Pay-Liam Lin; Yu-Chieng Liou; Yi-Hui Chang; Yu-Chih Huang; Lin Yi-Sheng (Atmospheric Research, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Exposure to contaminants of emerging concern and gestational diabetes mellitus subtypes: An exploratory nested case-control study - Boya Wang; Yiwen Qiu; Nuo Xu; Shuhui Wang; Xialidan Alifu; Haoyue Cheng; Hui Liu; Lina Yu; Zi Lin; Danqing Chen; Liqiong Guo; Yunxian Yu (Journal of Hazardous Materials, 2025)

Impact of KCl and L-Arg substitution on low salt beef patties: oxidative, textural, flavor, and microbial insights - Chuanlong Yu; Lingli Chen; Hui Chen; Suyun Lin; Wenbing Hu; Kehui Ouyang; Wenjun Wang (Food Chemistry, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

Integrated metabolomics reveals immunomodulatory compounds in giant African snail (Achatina fulica) extracts for the giant river prawn (Macrobrachium rosenbergii) - Youshang Lin; Chen-Hsun Liu; Chiu-Hui Kuo; Bonien Chen; Wei-Ming Wu; Tsung-Meng Wu; Te-Yu Liao; Kuohsun Chiu (Fish & Shellfish Immunology, 2025)

Synergistic exposure to endocrine-disrupting chemicals in pediatric lungs: Epidemiological drivers and disease-associated variations - Chunzhao Chen; Jie Yu; Hui Qi; Cuiying Zhong; Jian Tang; Chenghao Chen; Zheng Li; Xuemei Yang; Yujia Wu; Wanning Chen; Gang Yu; Lin Sun (Environmental Pollution, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Structural characterization and immunomodulatory activity of a novel pectin polysaccharide extracted from Gardenia jasminoides fruit - Yue Guo; Yanan Cheng; Bing Zheng; Jianhua Xie; Yi Chen; Huasi Lin; Hui Liu; Xiaobo Hu; Qiang Yu (Carbohydrate Polymers, 2025)

Multiple Mechanisms and Therapeutic Strategies for the Involvement of AMPK in the Development of Alzheimer’s Disease - Lin Yu; Xue Yang; Hui-Ping Lei; Yue-Ting Hu; Ling-Nan Wu; Shao-Yu Zhou; Feng Jin (Molecular Neurobiology, 2025)

Inverse Admittance Characteristics of Gastric Cancer Cells Measured by a Validated Dielectrophoretic Microfluidic Platform - Jia‑Jiun Tsai; Yun-Jung Tsai; Mei Yu Huang; Chun-Ping Jen; Shu-Hui Lin (Journal of Medical and Biological Engineering, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Two new amplisins with antibacterial activities from Akanthomyces attenuatus - Fan Cai; Wen Xie; Haoyu Yu; Xingtong Chen; Wei Lin; Jianbin Xiao; Chao Chen; Mingliang Zhang; Qin Li; Huaidong Zhang; Hui Zhang; Li Li (Natural Product Research, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Silicon isotope variations of ocean island basalts: the effect of recycled materials on Si isotopes in the mantle - Yu-Chao Lin; Hui-Min Yu; Matthew G. Jackson; Elisabeth Widom; David Kuentz; Fang Huang (Geochimica et Cosmochimica Acta, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Complex of butyric acid with the amorphous region of starch granules via high-pressure processing - Amy Hui-Mei Lin; Shaun Yong Jie Sim; Choy Eng Nge; Ting-Jang Lu; Nur Syahirah Amirruddin; Amanda Xin Yi Sng; Kai Ting Wong; Yoganathan Kanagasundaram; Andrea Gómez-Maqueo; Hui Yu Sim (Food Chemistry, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Methadone degradation and reduced nitrosamine formation in synthetic human urine by the photoelectrochemical process using GOTiO2 film photoelectrodes - Hai-Fei Yang; Jheng-Sian Yang; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Assessment for seawall modifications to mitigate land crabs roadkills from field experiments and agent-based modeling - Kuang-Yu Tseng; Yun-Ting Hsieh; Yu-Wen Chen; Ting-Yu Liang; Hui-Chen Lin (Journal of Environmental Management, 2025)

Process and mechanism of low-temperature molten salt roasting conversion of beryl ore: Towards low-energy-consumption beryllium smelting - Lin Yu; Xiaobo Min; Hui Xu; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Zhiyan Zeng; Yibin Xie; Cong Peng; Yong Ke (Journal of Environmental Chemical Engineering, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

One-pot tailored synthesis of highly monodisperse β-1,3-glucan from sucrose driven by an in vitro self-assembled dual-enzyme system via spy chemistry - Guotao Mao; Ming Song; Jin Yu; Junhan Lin; Zhanhe Wang; Zengping Su; Hui Xie; Hongsen Zhang; Hongge Chen; Andong Song (Carbohydrate Polymers, 2025)

Analysis of the relationship between C, N, P and dry matter content of 41 subtropical woody plants from seasonal and developmental scales - Zheng-Chao Yu; Xiao-Ting Zheng; Wei Lin; Wei He; Hui Zhu; Chang-Lian Peng (Trees, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Socioeconomic impacts linked to land use and land use changes affecting blue carbon ecosystems in Southeast Asia: A systematic map - Maryam Jamilah; Amani Becker; Soon Loong Lee; T.E. Angela L. Quiros; Su Yin Chee; Claire Evans; Yu Yang Tan; Lian Lin Ti; Irsyad Pishal; Amy Yee Hui Then (Ocean & Coastal Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A PLA2-responsive nanoagonist to boost immunotherapy via targeted release of lipid mediators in cold tumor microenvironment - Hui-Ping Wen; Meng-Die Zhu; Di Ning; Zhi-Gang Wang; Yusi Hu; Chuan-Ming Yu; Dai-Wen Pang; Shu-Lin Liu (Science Bulletin, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Seasonal characteristics, source apportionment and ecological risk assessment of priority and emerging contaminants using passive samplers in the coastal water - Zishan Diao; Xianyin Ping; Xue Zhang; Bin Hui; Fanping Zhu; Yiqiao Zhang; Jing Wang; Yinjie Yu; Lin Zhang; Wenjia Hui; Xiaomin Xie; Xiaohan Zhang; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Stand density influences soil organic carbon stocks and fractions by mediating soil biochemical properties in Mongolian pine plantations - Yansong Zhang; De-Hui Zeng; Zimeng Sheng; Qing-Wei Wang; Dapao Yu; Guigang Lin (Plant and Soil, 2025)

The CXCL8-CXCR2 axis promotes M2 macrophage polarization in ovarian cancer via RASGRP4-mediated mTOR-STAT3 signaling - Mi Ren; Ling-ling Chen; Lin-yin Jiang; Hui-hui Yu; Hai-zhou Ji (Apoptosis, 2025)

Deep learning reveals the relationship between vegetation and runoff in the Weihe River Basin on the Loess Plateau - Qin Ju; Wenjie Zhao; Tongqing Shen; Junliang Jin; Hui Lin; Xiaoni Liu; Peng Jiang; Jianhui Wei; Zhongbo Yu (Hydrological Sciences Journal, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Construction of PtFe/FeOx-Al2O3 interface via regulating the metal – support interactions for selective hydrogenation of cinnamaldehyde - Zequan Ma; Yilin Dong; Xu Tan; Jia Xue; Xiaoge Li; Yu Gu; Hui Shi; Lin-Wei Chen; Kun Wang; Lei Wang (Chemical Engineering Journal, 2025)

Divergence of Two Diospyros Species Promoted by Geo‐Climatic Processes Across Dry Valleys and Lowlands in Subtropical China - Yu‐Juan Zhao; Hui‐Hui Xi; Jiao Lin; Rui Yang; Gen‐Shen Yin; Xun Gong (Journal of Biogeography, 2025)
Aim Exploring the divergence and speciation processes is central to understanding the origin and maintenance of biodiversity. The dry valley mosaic in the Hengduan Mountains and its southern extension range is one of the special landscapes globally and harbours a high level of endemic plants of tropical margin nature. The dry valleys and lowlands‐adapted plants constitute a unique system to explore how the geological and ecological effects have shaped the speciation processes here. Location Subtropical China. Taxon Diospyros dumetorum and Diospyros saxatilis. Methods We surveyed patterns of genetic variation from 33 populations spanning their distribution ranges using three chloroplast DNA fragments and eight nuclear microsatellite loci. Approximate Bayesian computation was conducted to compare population demographic models considering gene flow and to estimate key parameters. We used Ecological Niche Models (ENMs) to reconstruct changes in range distribution during glacial and interglacial periods and evaluate their niche differentiation. Results Plastid and nuclear data strongly support divergence between the two species occurring during the Pliocene/Pleistocene period followed by secondary contact in response to climatic oscillations. ENMs predicted drastic distribution range changes during the Quaternary and identified significant differences in climatic conditions at the set of locations occupied by these two species. Correlation analyses were conducted, and the results suggest that geographical isolation rather than environmental heterogeneity shapes the current population genetic structure within the two species. Main Conclusion Phylogeographical patterns revealed in our results document that geographic vicariance associated with tectonic uplifts initiated allopatric species divergence between the two dry valleys and lowlands‐adapted Diospyros species, and niche differentiation perhaps further accelerated the speciation processes with limited subsequent gene flow. Our findings could contribute to the knowledge of forces that drive speciation processes in the unique landscape of dry valleys, as well as the evolution of the flora in subtropical China.

Rodent Bioturbation Significantly Enhances Annual Methane Uptake by Tibetan Alpine Grasslands - Dezhao Gan; Dongsheng Yu; Hongchao Zuo; Zheng Li; Zelong Zhang; Huinan Li; Zhenrong Lin; Hui Wang; Qingping Zhou; Jinsong Wang; Shuli Niu; Ruijun Long; et al. (Global Change Biology, 2025)
Tibetan alpine grasslands (AG) serve as critical methane (CH 4 ) sinks, yet face degradation from anthropogenic and climatic disturbances that promote subterranean rodents (e.g., Plateau zokor [ Myospalax baileyi ] and pika [ Ochotona curzoniae ]) activities. Although rodent bioturbation (e.g., burrowing, foraging and excreting) alters soil structure, soil physico‐chemical properties and productivity from AG, its impacts on CH 4 uptake remain poorly understood. Among the first, we combined paired year‐round CH 4 flux measurements from Plateau zokor mounds (ZM) and surrounding healthy meadow (HM) patches in Tibetan alpine meadow with collated CH 4 fluxes from meta‐ and synthetic analyses across Tibetan AG, temperate grasslands (TG) and tropical grasslands (TrG) globally. We observed that rodent bioturbation significantly ( p 4 uptake (HM: −0.91 ± 0.08 kg C ha −1 vs. ZM: −1.80 ± 0.19 kg C ha −1 , mean ± standard error, negative values indicate uptake). Notably, 67% of this net increase (−0.89 ± 0.10 kg C ha −1 year −1 ) due to rodent bioturbation occurred during the growing season. Meta‐analysis results revealed this phenomenon associated with significantly ( p pmoA for methanotrophs. Non‐growing season (NGS) CH 4 uptake contributed 45% and 39% to annual CH 4 uptake for HM and ZM, respectively, falling into the ranges of 12%–64% NGS CH 4 uptake contributions from TG to AG of China. The TrG showed significant ( p 4 uptake than TG and AG globally, due to the fact that significant ( p 4 flux changes and highlight soil moisture as a key driver for global CH 4 sink variations. These results emphasise the need for long‐term monitoring to better assess the ecological consequences of bioturbation in climate‐sensitive alpine ecosystems.

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

A novel catalytic ozonation mechanism of MIL-53(Fe70Ce30): Role of abundant oxygen vacancies and unsaturated metal centers generated via Ce-doping - Hui Yu; Xiaochuan Lin; Shuxin Ren; Kaiyang Chen; Quan Sun; Min Song; Chaoqun Tan (Chemical Engineering Journal, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from Dendrobium huoshanense and their chemotaxonomic significance - Huan Liu; Hui Yang; Bai-Lin Su; Bo-Wei Li; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Targeting ferroptosis for precision medicine in cervical cancer - Xin Sun; Zhuoxi Chen; Hui Yang; Jianing Yu; Haiyan Lin; Leiming Zhang (Apoptosis, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Ecological disposal of bauxite tailings and red mud: A sustainable strategy for bauxite industrial waste reuse - Xusheng Jiang; Xuehong Zhang; Xijun Liu; Hui Qiu; Mengting Lin; Guo Yu; Shouhui Zhang; Jie Liu (Resources, Conservation and Recycling, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Tunning “closed-loop” pockets for constructing stabilized structures of nanobody in the detection of procymidone under a broad range of pH value - Hui-Wei Huang; Aori Qileng; Lin Luo; Yu Wang; Song Huang; Yu-Dong Shen; Min-Ling Liu; Zhen-Lin Xu (Food Chemistry, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Enhancing the Fe3+/Fe2+ biocatalytic cycle using deoxidizing and iron-releasing sticks to improve bio-fenton efficiency - Chi-Wen Lin; Chung-Yen Yeh; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Drying-rewetting cycles decrease temperature sensitivity of soil organic matter decomposition - Junjie Lin; Wenling Zhang; Amit Kumar; Dafeng Hui; Changai Zhang; Shengdao Shan; Zhiguo Yu; Biao Zhu; Yakov Kuzyakov (Agricultural and Forest Meteorology, 2025)

Chronological and palaeoecological insights into the Dayakou fauna in Yanjinggou, Chongqing, China: Responses of large mammals to the Early-Middle Pleistocene Climate Transition - Haiqian Hu; Haowen Tong; Fei Han; Hui Dai; Wanbo Huang; Qigao Jiangzuo; Paul Rummy; Xunqian Wang; Yu Lin; Guangbiao Wei (Quaternary Science Reviews, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Enhanced reaction kinetics of sterically hindered amines in semi-aqueous N-methyl-2-pyrrolidone for CO2 capture - Chi-Hui Cheng; Yu-Fan Chen; Yu-Jeng Lin (Chemical Engineering Journal, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Sustainable and selective upgrade of Cu(II) to High-Value HKUST-1 from acidic electroplating wastewater - Lin Ding; Qiang Wang; Yu Luo; Yunxia Luo; Wei Ren; Hui Shi; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A new late-diverging non-hadrosaurid hadrosauroid (Dinosauria: Ornithopoda) from southwest China: Support for interchange of dinosaur faunas across East Asia during the Late Cretaceous - Hui Dai; Qingyu Ma; Can Xiong; Yu Lin; Hui Zeng; Chao Tan; Jun Wang; Yuguang Zhang; Hai Xing (Cretaceous Research, 2025)

Concentration-dependent effect of norfloxacin on iron toxicity in the intestine of large yellow croaker Larimichthys crocea (Richardson, 1846) - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Liu; Min-Hui Yu; Hui Zhang; Fei Li (Frontiers in Marine Science, 2025)
This study explores the effects of norfloxacin (NOR) on oxidative damage, iron (Fe) transport, energy metabolism, and immunotoxicity in the intestine of large yellow croaker under Fe stress. The fish were subjected to Fe (180 μg/L), low-dose NOR (1.8 μg/L, LNOR), high-dose NOR (180 μg/L, HNOR), Fe plus LNOR, and Fe plus HNOR for 60 days. These results demonstrated that Fe alone exposure increased malondialdehyde (MDA), protein carboxylation (PC), and mortality rate, and impaired intestinal tissue, which was related to the increment of Fe accumulation. Compared to Fe alone exposure, Fe plus LNOR exposure decreased MDA, PC, and mortality rate, and alleviated intestinal malformations by improving Fe transport, energy metabolism, anti-inflammatory response, and protein folding protective effect, and reducing pro-inflammatory response, indicating that LNOR had an antagonistic effect on Fe toxicity. Compared to Fe alone exposure, Fe plus HNOR exposure elevated MDA, PC, and mortality rate, and deteriorated intestinal malformations by inhibiting Fe excretion, energy metabolism, anti-inflammatory response, and protein folding protective effect, and enhancing pro-inflammatory response, indicating a synergetic effect between HNOR and Fe stress. These findings suggested that NOR had a dose-dependent effect on Fe-toxicity to large yellow croaker, which contributes to revealing the molecular mechanisms behind their interaction and its ecological implications.

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Novel antibody- and aptamer-based approaches for sensitive detection of mycotoxin fusaric acid in cereal - Shih-Wei Wu; Chia-Yu Hsieh; Biing-Hui Liu; Xin-Jie Lin; Feng-Yih Yu (Food Chemistry, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Reactive oxygen species-sensitive fenofibrate-loaded dextran nanoparticles in alleviation of osteoarthritis - Weibei Sheng; Shuai Liao; Siyang Cao; Yihao Wei; Jin Zhao; Yaohang Yue; Haotian Qin; Tiantian Qi; Junyu Qian; Jianjing Lin; Jian Weng; Yingqi Chen; et al. (Carbohydrate Polymers, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Sulforaphane acts through the NFE2L2/AMPK signaling pathway to protect boar spermatozoa from cryoinjury by activating antioxidant defenses - Guangzhi Zhang; Fei Wen; Yu Li; Pingyu Sun; Yang Li; Zhangtao Hu; Hui Wang; Yunhui Ma; Guodong Liang; Lin Chen; Ke Yang; Jianhong Hu (Theriogenology, 2024)

New insights into the stages of cadmium remediation in ryegrass enhanced by kitchen compost-derived dissolved organic matter: Activation, absorption, and storage - Bing Kou; Lin Huo; Minyi Cao; Kunlong Hui; Wenbing Tan; Ying Yuan; Yu Jiang (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Lake responses and mechanisms to El Niño on the Tibetan Plateau using deep learning-based semantic segmentation - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen; Jingcai Wang (Journal of Hydrology, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Interactions between microplastics and heavy metals in leachate: Implications for landfill stabilization process - Jiabao Chen; Lin Huo; Ying Yuan; Yu Jiang; Hui Wang; Kunlong Hui; Yanjiao Li; Zekai Huang; Beidou Xi (Journal of Hazardous Materials, 2024)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

The mining of thermostable β-glucosidase for tea aroma enhancement under brewing conditions - Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Yongquan Xu; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Removal and recovery of nitrogen from anaerobically treated leachate based on a neglected HNAD nitrogen removal pathway: NH3 stripping - Facai An; Yunfei Gao; Maomin Yu; Tianxiao Xiao; Hui Lin; Dezhi Sun (Bioresource Technology, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Positive Association Between Serum Concentration of 4-Tertiary-octylphenol and Oxidation of DNA and Lipid in Adolescents and Young Adults - Chien-Yu Lin; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

A systematic evaluation of population pharmacokinetic models for polymyxin B in patients with liver and/or kidney dysfunction - Xueyong Li; Yu Cheng; Bingqing Zhang; Bo Chen; Yiying Chen; Yingbing Huang; Hailing Lin; Lili Zhou; Hui Zhang; Maobai Liu; Wancai Que; Hongqiang Qiu (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

On the Revival Mechanism of Typhoon Doksuri (2023) Remnants after Its Landfall - Chunyi Xiang; Lin Dong; Yu Lan; Hui Wang; Runling Yu; Xiaoyong Zhuge; Da Liu; Qian Wang (Journal of Meteorological Research, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Performance and biotoxicity of electro-Fenton treatment of bisphenol A: Evaluation of copper recovered from microbial fuel cell cathodes for subsequent catalytic applications - Chi-Wen Lin; Guan-Yi Chen; Shu-Hui Liu; Wei Tong Chen; Shih-Hsien Chang; Chih-Yu Ma (Process Safety and Environmental Protection, 2024)

Impacts of shellfish and macroalgae mariculture on the seawater carbonate system and air-sea CO 2 flux in Haizhou Bay, China - Jia-Hui Zhou; Ying-Zi Guo; Xu Zhao; Jin-Chen Yu; Jin Zhou; Jun Lin; Hong Huang (Marine Environmental Research, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Applying kitchen compost promoted soil chrysene degradation by optimizing microbial community structure - Bing Kou; Lin Huo; Minyi Cao; Tingqiao Yu; Yuman Wu; Kunlong Hui; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Effect of partial substitution of NaCl by KCl on aggregation behavior and gel properties of beef myosin - Chuanlong Yu; Lingli Chen; Kehui Ouyang; Hui Chen; Mingsheng Xu; Suyun Lin; Wenjun Wang (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Interface-Confined nanocatalysts at hollow porous nanofibers for High-Performance cascaded remediation of radioactive wastewater - Qi-Hui Ye; Hao Ye; Yu-Cong Yu; Xiao-Lin Wang; Qiao Luo; Ming-Bang Wu; Juming Yao (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Dynamic Response Prediction Model for Jack-Up Platform Pile Legs Based on Random Forest Algorithm - Xiaohui Cui; Hui Liu; Xiang Lin; Jiahe Zou; Yu Wang; Bo Zhou (Journal of Marine Science and Engineering, 2024)
Jack-up offshore platforms are widely used in many fields, and it is of great importance to quickly and accurately predict the dynamic response of platform pile leg structures in real time. The current analytical techniques are founded upon numerical modelling of the platform structure. Although these methods can be used to accurately analyze the dynamic response of the platform, they require a large quantity of computational resources and cannot meet the requirements of real-time prediction. A predictive model for the dynamic response of the pile leg of a jack-up platform based on the random forest algorithm is proposed. Firstly, a pile leg dynamic response database is established based on high-fidelity numerical model simulation calculations. The data are subjected to cleaning and dimensional reduction in order to facilitate the training of the random forest model. Cross-checking and Bayesian optimization algorithms are used for the selection of random forest parameters. The results show that the prediction model is capable of outputting response results for new environmental load inputs within a few milliseconds, and the prediction results remain highly accurate and perform well at extreme values.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Examining the impact of polyfluoroalkyl substance exposure on erythrocyte profiles and its related nutrients: Insights from a prospective study on young Taiwanese - Chien-Yu Lin; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Environmental Pollution, 2024)

Numerical study of energy consumption in spacer-filled feed channels through 3D inverse modeling and computational fluid dynamics - Hui Guan; Jiacheng Li; Doufeng Wu; Sanchuan Yu; Peifeng Lin; Xiao Hu (Desalination, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Examining a decade-long trend in exposure to per- and polyfluoroalkyl substances and their correlation with lipid profiles: Insights from a prospective cohort study on the young Taiwanese population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Chemosphere, 2024)

Local adaptation of trophic strategy determined the tolerance of coral Galaxea fascicularis to environmental fluctuations - Xiao-Lei Yu; Cheng-Yue Liu; Lei Jiang; Lin-Tao Huang; Yong Luo; Pan Zhang; Yu-Yang Zhang; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Assessment of the antimicrobial and immunomodulatory activity of QS-CATH, a promising therapeutic agent isolated from the Chinese spiny frogs (Quasipaa spinosa) - Wei-Cheng Zheng; Xiao-Yun Cheng; Yu-Hui Tao; Yue-Song Mao; Cheng-Pu Lu; Zhi-Hua Lin; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Machine learning prediction on wetland succession and the impact of artificial structures from a decade of field data - Kuang-Yu Tseng; Yun-Ting Hsieh; Hui-Chen Lin (Science of The Total Environment, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Two new di-tert-butyl-type compounds from a saline-lake derived Streptomyces sp. XZB42 - Ya-Lin Yu; Shuang Chen; Jie-Bin Fang; Xiao-Ming Chen; Xin-Yi Tang; Jin-Hui Wang (Natural Product Research, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

Evaluation of spatial and temporal changes in illicit drug use in the Taipei metropolitan area via wastewater-based epidemiology - Hank Hui-Hsiang Lin; Yu-Hsiang Wang; Jennifer Ia Wen Wen Liu; Ming-Chi Hsieh; Shu-Jie Huang; En Lien; Li-Wei Huang; Angela Yu-Chen Lin (Science of The Total Environment, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

A systematic study on the chemical model of polycyclic aromatic hydrocarbons formation from nutrients (glucose, amino acids, fatty acids) in food - Qiuyi Lin; Haolin Zhang; Xiaomei Lv; Ruiwei Xie; Bing-Huei Chen; Yu-Wen Lai; Lei Chen; Hui Teng; Hui Cao (Food Chemistry, 2024)

Exploring the roles of excess amino acids, creatine, creatinine, and glucose in the formation of heterocyclic aromatic amines by UPLC-MS/MS - Haolin Zhang; Xiaomei Lv; Weiming Su; Bing-Huei Chen; Yu-Wen Lai; Ruiwei Xie; Qiuyi Lin; Lei Chen; Hui Cao (Food Chemistry, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Sunlight enhanced the formation of tribromomethane from benzotriazole degradation during the sunlight/free chlorine treatment in the presence of bromide - Ming-Chi Hsieh; Wan-Ning Lee; Yi-Hsuan Chu; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemosphere, 2024)

Differential effects of oxytetracycline on detoxification and antioxidant defense in the hepatopancreas and intestine of Chinese mitten crab under cadmium stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Zhang; Hui Zhang; Zi-Ming Liu; Min-Hui Yu; Bing Hu (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Experimental investigation on the flow boiling of R134a in a plate heat exchanger with mini-wavy corrugations - Wei-chao Lao; Yi-dong Fang; Qing-hu Chen; Lin-jie Xu; Hui-nan Yang; Yu-qi Huang (International Journal of Refrigeration, 2024)

Enhanced lanthanum and cerium removal of self-powered electro-membrane bioreactor (SPEMBR) using high-active bi-functional M-N-CNTs@Fe/Mo electrode - Hui Lu; Hongbo Wang; Changfei Gao; Lifen Liu; Tingting Yu; Yihua Li; Shaoying Lin (Chemical Engineering Journal, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

A novel strategy for enhancing the stability of aptamer conformations in heavy metal ion detection - Shi Quan Qian; Min Yuan; Xian Wei Zuo; Hui Cao; Jin Song Yu; Li-Ling Hao; Kun Lin Yang; Fei Xu (Analytica Chimica Acta, 2024)

Deblurring Network for UV Images of Colorless Chemicals Floating on Sea Surface - Hui Huang; Yu Zhang; Chuansong Lin; Fuliang Lin; Yue Fang; Hong Song (Journal of Marine Science and Engineering, 2024)
Automatic imaging monitoring technology has been developed as a mature solution to address oil spill accidents. However, when airborne equipment is used to monitor the area of leakage, there is a chance of relative motion between the equipment and the target, leading to blurred images. This can hinder subsequent monitoring tasks, such as the identification and segmentation of hazardous chemical targets. Therefore, it is crucial to deblur these images, as sharper images can substantially improve the precision and accuracy of these tasks. In light of this, this paper presents a novel multi-scale recurrent deblurring network, leveraging the Convolutional Block Attention Module (CBAM) attention mechanism, to restore clear images in an end-to-end manner. The CBAM attention mechanism has been incorporated, which learns features in both the spatial and channel domains, thereby enhancing the deblurring ability of the network by combining the attention mechanisms of multiple domains. To evaluate the effectiveness of the proposed method, we applied the deblurring network to our self-built dataset of blurred ultraviolet (UV) images of colorless chemicals floating on water surfaces. Compared to the SRN-Deblur deblurring network, the proposed approach yields improved PSNR and SSIM results. Moreover, when compared with the state-of-the-art DeblurGANv2 method, it performs better in the SSIM. These results demonstrate that the proposed multi-scale recurrent deblurring network, based on the CBAM attention mechanism, exhibits a superior deblurring performance.

Corrigendum to “Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases” [Sci. Total Environ. 925 171492] - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

Effects of polystyrene microplastics on the metabolic level of Pseudomonas aeruginosa - Hui Tao; Lingqin Zhou; Duo Yu; Yiyang Chen; Yunxin Luo; Tao Lin (Science of The Total Environment, 2024)

Life-stage specificity and temporal variations in transcriptomes and DNA methylomes of the reef coral Pocillopora damicornis in response to thermal acclimation - Lei Jiang; Pan Zhang; Lin-Tao Huang; Xiao-Lei Yu; Cheng-Yue Liu; Xiang-Cheng Yuan; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Improving time-series InSAR deformation estimation for city clusters by deep learning-based atmospheric delay correction - Peifeng Ma; Chang Yu; Zeyu Jiao; Yi Zheng; Zherong Wu; Wenfei Mao; Hui Lin (Remote Sensing of Environment, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Visible light-mediated supramolecular framework for tunable CO2 adsorption - Tao Yang; Chunyi Yu; Chen Gu; Yang Liu; Hui Wen; Xiao-Qin Liu; Guoliang Liu; Lifeng Ding; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Glyphosate drives autophagy-dependent ferroptosis to inhibit testosterone synthesis in mouse Leydig cells - Lu Lu; Cai-Yu Lian; Yan-Ting Lv; Shu-Hui Zhang; Long Wang; Lin Wang (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Solar-driven persulfate degradation of caffeine and cephradine in synthetic human urine - Wei-Ming Kung; Hank Hui-Hsiang Lin; Yu-Hsiang Wang; Angela Yu-Chen Lin (Journal of Hazardous Materials, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Rapid identification and characterization of pineapple fruitlet core rot pathogens on the ‘TN20’ cultivar in Taiwan - Yu-Ping Liang; Kuan-Yu Lin; Su-Yu Lai; Hui-Fang Ni (European Journal of Plant Pathology, 2024)

Functional connectivity disruption of insular subregions in the cirrhotic patients with minimal hepatic encephalopathy - Hong-Yu Lin; Hui-Wei Huang; Qiu-Yi Dong; Li-Min Cai; Hua-Jun Chen (Brain Imaging and Behavior, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Numerical investigation of a semi-submersible platform interacting with steep waves using a fully nonlinear method - Zi-Lin Zhang; Shi-Li Sun; Bo-Yu Chen; Hui-Long Ren (Ocean Engineering, 2024)

Peracetic acid as an alternative disinfectant for micropollutants degradation and disinfection byproducts control in outdoor swimming pools - Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Journal of Hazardous Materials, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

β-Lapachone induces ferroptosis of colorectal cancer cells via NCOA4-mediated ferritinophagy by activating JNK pathway - Lei Zhao; Hui Miao; Mingqi Quan; Shuhao Wang; Yu Zhang; Houkun Zhou; Xianglan Zhang; Zhenhua Lin; Junjie Piao (Chemico-Biological Interactions, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Microbial metabolic flexibility guarantees function resilience in response to starvation disturbance - Yong-Chao Wang; Ya-Hui Lv; Xu-Rui Hu; Yu-Ting Lin; John C. Crittenden; Can Wang (Bioresource Technology, 2024)

Three new coumarin derivatives from Maytenus hookeri - Lingjie Meng; Changyan Yu; Jing Hui; Nian Jiang; Haijuan Wang; Jianxun Xie; Lin Xu; Yun Liu (Natural Product Research, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Hydrological connectivity controls on the dynamics of particulate organic matter in a semi-enclosed mariculture bay - Aiqin Han; Jin-Yu Terence Yang; Mengli Chen; Zhenzhen Zheng; Xijie Yin; Hui Lin; Min Nina Xu; Shuh-Ji Kao (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Effects of elevated temperature and copper exposure on the physiological state of the coral Galaxea fascicularis - Meng Cheng; Yong Luo; Xiao-Lei Yu; Lin-Tao Huang; Jian-Sheng Lian; Hui Huang (Marine Environmental Research, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Scenarios of temporal environmental alterations and phytoplankton diversity in a changing bay in the East China Sea - Yu Wang; Weibo Wang; Yaqin Huang; Lin Chang; Xiaoming Tang; Xuebao He; Hui Lin (Frontiers in Marine Science, 2023)
In the context of global change, the stressors of warming and eutrophication have significant ecological implications in coastal waters. In order to examine the diversity of phytoplankton and its relationship with water quality, we conducted a survey of phytoplankton community compositions and their correlation with environmental changes over four seasons in a eutrophic bay located in the East China Sea. Through a systematic analysis, we identified diatoms and dinoflagellates as the primary dominant groups, with the species Skeletonema costatum , Skeletonema marinoi , Biddulphia sinensis , Thalassiosira eccentrica , Leptocylindrus danicus , Coscinodiscus oculus-iridis , Coscinodiscus jonesianus , and Chaetoceros knipowitschi as the most abundant species in all seasons. Significant seasonal alterations were observed in both environmental settings and phytoplankton species richness, dominance, and abundance. The phytoplankton community varied in its response to diverse aquatic environments and was principally affected by temperature, silicic acid concentrations, and suspended solids. Elevated temperatures were found to promote an increase in phytoplankton abundance. However, no clear evidence of diatom and dinoflagellate succession in relation to N:P ratio was observed across seasons. Water quality analysis illustrated that the majority of the study area exhibited a mid-eutrophic with severe organic pollution. The abundance of phytoplankton was significantly influenced by eutrophication and organic pollution. The accelerated warming process related to coastal nuclear power plants and nutrient regime alterations significantly affect the temporal shift of the phytoplankton community. These findings contribute valuable insights into the effects of eutrophic environments on the structure of phytoplankton communities in coastal aquatic systems.

Combined effects of microcystin-LR and rice straw-derived biochar on the hepatic antioxidant capacity of zebrafish: Insights from LC-MS/MS-based metabolomics analysis - Wang Lin; Kang Ouyang; Ya He; Hui Yang; Yu Kuang; Dapeng Li; Li Li (Science of The Total Environment, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

FePO4 preparation and residue recycling by co-processing of steelmaking slag and steel pickling waste liquor: Comprehensive utilization of metallurgical wastes - Yao-hui Yu; Chuan-ming Du; Jia-lin Jiang; Xin Wang (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Role of feeding and physiological trade-offs in sustaining resilience of the coral Galaxea fascicularis to light limitation - Xiao-Lei Yu; Lei Jiang; Yong Luo; Cheng-Yue Liu; Yu-Yang Zhang; Lin-Tao Huang; Pan Zhang; Xiang-Cheng Yuan; Hui Huang (Coral Reefs, 2023)

Frozen carbon is gradually thawing: Assessing interannual dynamics of thawed soil organic carbon stocks in the Tibetan Plateau permafrost area from 1901−2020 - Tongqing Shen; Peng Jiang; Qin Ju; Xuegao Chen; Hui Lin; Jiahui Zhao; Fan Zhang; Zhongbo Yu (Agricultural and Forest Meteorology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Spatial-temporal dynamics of meteorological and soil moisture drought on the Tibetan Plateau: Trend, response, and propagation process - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen (Journal of Hydrology, 2023)

Study on potential antigenicity and functional properties of whey protein treated by high hydrostatic pressure based on structural analysis - Xin-Xin Yu; Xiao-Hui Wang; Sheng-Ao Zhang; Ying-Hua Zhang; Han-Lin Zhang; Yu-Qi Yin (Food Research International, 2023)

Molecular and functional characterization of viperin in golden pompano, Trachinotus ovatus - Lin Huang; Xiaowen Zhu; Jihui Kuang; Bohuan Li; Qing Yu; Mingzhu Liu; Bingzheng Li; Hui Guo; Pengfei Li (Fish & Shellfish Immunology, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Design and Optimization of a New Type of Magnetic Suspension Vibration Absorber for Marine Engineering - Changming Dai; Zhengyuan Liu; Yu Wang; Xiang Lin; Hui Liu; Bo Zhou (Journal of Marine Science and Engineering, 2023)
The magnetic suspension damper, which is based on magnetic suspension technology, is receiving more and more attention from academics as active–passive hybrid damping technology develops. A new symmetric magnetic suspension structure is constructed in this study, and the accuracy of the simulation findings is confirmed by contrasting the output from finite element simulation with the theoretical formulations. On the basis of this, how the structure, size, and material of the electromagnet and armature affect the magnetic flux density, electromagnetic force, and suspension force is investigated. The structure optimization of the electromagnet and armature was performed in accordance with the simulation results, and a new symmetric magnetic suspension structure was produced. The results of the simulation demonstrate that DT4(electrical pure iron) is the ideal material for armatures and electromagnets. The reinforcing ring construction can be built up by the armature to increase suspension force. The suspension force output by the armature will be greatly increased when the size and placement of the reinforcing ring structure are right. The system stiffness adjustment range will expand at this point, enhancing the magnetic suspension damper’s functionality. This study offers novel perspectives for designing structures that reduce vibration and noise in various projects and serves as a guide to constructing magnetic suspension dampers.

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Inoculation of sulfate-reducing bacteria with a microbial fuel cell to treat groundwater that contains sulfolane: Improving performance, by-products and a biotoxicity assessment - Chi-Wen Lin; Yen-Hua Tseng; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

Prevalence of antimicrobial resistance in a full-scale drinking water treatment plant - Qihui Gu; Tao Lin; Xianhu Wei; Youxiong Zhang; Shi Wu; Xiaojuan Yang; Hui Zhao; Chufang Wang; Juan Wang; Yu Ding; Jumei Zhang; Qingping Wu (Journal of Environmental Management, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Dynamic pore modulation of contracted carbon fiber filter for wastewater treatment: Filtration performance and in-situ regeneration mechanism - Tao Xu; Lin Shi; Senlin Shao; Hui Wang; Yu Huang; Lei Xing; Re Xia; Ruggero Rossi; Liandong Zhu; Hua Zhu; Wulin Yang; Xuhui Mao; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Dynamic characteristics of heavy metal accumulation in agricultural soils after continuous organic fertilizer application: Field-scale monitoring - Wanchun Sun; Jing Ye; Hui Lin; Qiaogang Yu; Qiang Wang; Zhaoming Chen; Jinchuan Ma; Junwei Ma (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Increased styrene vapor removal and power production by adding silicone oil to microbial fuel cell-based trickling filter - Wen-Hua Lin; Shu-Hui Liu; Chih-Yu Ma; Chi-Wen Lin (Process Safety and Environmental Protection, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Ratiometric SERS imaging for indication of peroxynitrite fluctuations in diabetic wound healing process - Hui Chen; Shanshan Lin; Dianqi Zhang; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

Gut microbiota and ionizing radiation-induced damage: Is there a link? - Yueqiu Yu; Xiang Lin; Feiyang Feng; Yuanyun Wei; Shuang Wei; Yaqi Gong; Caimao Guo; Qingyu Wang; Peimeng Shuai; Tiantian Wang; Hui Qin; Guoqing Li; et al. (Environmental Research, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Simultaneously optimizing radiative decay and up-conversion of triphenylamine-based thermally activated delayed fluorescence emitters to achieve efficient deep-red organic light-emitting diodes - Hao-Yu Yang; Heng-Yuan Zhang; Ming Zhang; Hao Zhuo; Hui Wang; Hui Lin; Si-Lu Tao; Cai-Jun Zheng; Xiao-Hong Zhang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Ecofriendly removal of Lead, Cadmium and Arsenic along with turbidity from contaminated water using natural reservoir clay (NRC) and S. pasteurii derived urease - Jyoti Prakash Maity; Yung-Ping Chen; Jirawadee Promsri; Yi-Hsun Huang; Raju Kumar Sharma; Yu-Hui Chen; Pin-Yun Lin; Marut Tangwattanachuleeporn; Kulwara Poolpol; Tsung-Hsien Chen; Chien-Yen Chen (Desalination, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

p-y based approach to predicting the response of monopile embedded in soft clay under long-term cyclic loading - Chi-Chin Tsai; Yu-Pai Li; Sheng-Hui Lin (Ocean Engineering, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Glyphosate-induced autophagy inhibition results in hepatic steatosis via mediating epigenetic reprogramming of PPARα in roosters - Cai-Yu Lian; Sheng Wei; Zi-Fa Li; Shu-Hui Zhang; Zhen-Yong Wang; Lin Wang (Environmental Pollution, 2023)

Silicon isotopic compositions of altered Oceanic crust samples from IODP U1365 and U1368: Effect of low-temperature seawater alteration - Hui-Min Yu; Lin Yang; Guo-Liang Zhang; Fang Huang (Chemical Geology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane - Shao-Heng Chang; Chi-Wen Lin; Yu-Shen Cheng; Shu-Hui Liu (Chemosphere, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Planetary cross-linked structure design of hybrid organosilica membrane by amine-driven polymerization for CO2 separation - Jing-Yi Li; Yu-Ting Lin; David K. Wang; Hui-Hsin Tseng; Ming-Yen Wey (Journal of Cleaner Production, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Dynamic change of oligopeptides and free amino acids composition in five types of tea with different fermentation degree processed from the same batch of fresh tea (Camelilia Sinensis. L.) leaves - Feng Zhao; Wenxi Wu; Chi Wang; Xiaojuan Wang; Hui Liu; Jiang Qian; Chunping Cai; Yong Xie; Yu Lin (Food Chemistry, 2023)

Shrub encroachment increases soil erosion risk in hillside alpine meadows of the Qinghai-Tibetan Plateau, NW China - Yi-Fan Liu; Hui Fang; Ze Huang; Pedro A.M. Leite; Yu Liu; Manuel López-Vicente; Jingxue Zhao; Zhi-Hua Shi; Gao-Lin Wu (CATENA, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

Changes in permafrost spatial distribution and active layer thickness from 1980 to 2020 on the Tibet Plateau - Tongqing Shen; Peng Jiang; Qin Ju; Zhongbo Yu; Xuegao Chen; Hui Lin; Yueguan Zhang (Science of The Total Environment, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

Environmental laws and ecological restoration projects enhancing ecosystem services in China: A meta-analysis - Tao Liu; Le Yu; Xin Chen; Hui Wu; Hui Lin; Chengxiu Li; Jiaru Hou (Journal of Environmental Management, 2023)

Solar photodegradation of the UV filter benzotriazole in the presence of persulfate - Shih-Chieh Lai; Hank Hui-Hsiang Lin; Jheng-Sian Yang; Ming-Chi Hsieh; Angela Yu-Chen Lin (Journal of Environmental Chemical Engineering, 2023)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Lactoferrin attenuated urban particulate matter-induced nephrotoxicity by regulating the CSF2/CENPE axis - Wen-Chih Liu; Hui-Wen Chiu; Chu-Lin Chou; Yu-Jhe Chiu; Yu-Hsuan Lee (Environmental Pollution, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Sulfur isotope, fluid inclusions, and quartz solubility model decipher multistage hydrothermal fluids evolution and ore precipitation mechanism at the Nantai porphyry Mo deposit, Qinling, Central China - Zhong-Yu Zhang; Yin-Hong Wang; Jia-Jun Liu; Shan-Yuan Lin; Fang-Fang Zhang; Wei Zhang; Zhen-Yu Bo; Hui Zhang; Hong-Yu Li (Chemical Geology, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Degradation of poly(butylene adipate-co-terephthalate) films by Thermobifida fusca FXJ-1 isolated from compost - Xianbo Jia; Ke Zhao; Jie Zhao; Chenqiang Lin; Hui Zhang; Longjun Chen; Jichen Chen; Yu Fang (Journal of Hazardous Materials, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Regulation of enzymatic and non-enzymatic antioxidants in rice seedlings against chromium stress through sodium hydrosulfide and sodium nitroprusside - Yu-Juan Lin; Xing-Hui Feng; Yu-Xi Feng (Environmental Science and Pollution Research, 2022)

Protective effect of ginsenoside Rd on military aviation noise-induced cochlear hair cell damage in guinea pigs - Xue-min Chen; Yu-hui Liu; Shuai-fei Ji; Xin-miao Xue; Lin-lin Wang; Min Zhang; Yao-ming Chang; Xiao-cheng Wang (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Nutrient distributions and nitrogen-anomaly (N*) in the tropical North Pacific Ocean - Aiqin Han; Yu Wang; Yunlong Huo; Cai Lin; Kaiwen Zhou; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Gregarious larval settlement mediates the responses of new recruits of the reef coral Acropora austera to ocean warming and acidification - Lei Jiang; Yu-Yang Zhang; Cheng-Yue Liu; Lin-Tao Huang; Hao-Ya Tong; Guo-Wei Zhou; Ming-Lan Guo; Tao Yuan; Hui Huang (Frontiers in Marine Science, 2022)
Gregarious larval settlement represents an important window for chimera formation in reef corals, yet it remains largely unknown how aggregated settlement and early chimerism could modify the performance and responses of coral recruits under elevated temperature and p CO 2 . In this study, single and aggregated recruits of the broadcast spawning coral Acropora austera were exposed to contrasts of two temperatures (28 versus 30.5°C) and p CO 2 levels (~500 versus 1000 μatm) for two weeks, and algal symbiont infection success, survivorship and growth were assessed. Results showed that symbiont infection success was mainly affected by temperature and recruit type, with reduced symbiont infection at increased temperature and consistently higher infection success in chimeric recruits compared to single recruits. Furthermore, although chimeric recruits with larger areal size had significantly higher survivorship in all treatments, the polyp-specific growth rates were considerably lower in chimeric entities than individual recruits. More importantly, the recruit type significantly influenced the responses of recruit polyp-specific growth rates to elevated temperature, with chimeras exhibiting lowered skeletal lateral growth under elevated temperature. These results demonstrate the benefits and costs associated with gregarious larval settlement for juvenile corals under ocean warming and acidification, and highlight the ecological role of larval settlement behavior in mediating the responses of coral recruits to climate change stressors.

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

CREB1 contributes colorectal cancer cell plasticity by regulating lncRNA CCAT1 and NF-κB pathways - Bin Li; Lisi Zheng; Jiayi Ye; Chenmin Zhang; Jie Zhou; Qiaojuan Huang; Yanhua Guo; Luqin Wang; Peng Yu; Shurong Liu; Qiao Lin; Yuxia Luo; et al. (Science China Life Sciences, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Transformation of HBCDs by Rhodococcus sp. stu-38 - Fei Yu; Wenqi Luo; Yuyang Li; Shanshan Meng; Xianbin Lin; Lele Li; Xueying Ye; Hui Wang; Tao Peng; Tongwang Huang; Zhong Hu (Current Microbiology, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Use of piggyBac Transposon System Constructed Murine Breast Cancer Model for Reporter Gene Imaging and Characterization of Metastatic Tumor Cells - Ying-Ling Chen; Yung-Cheng Wang; Kuei-Yuan Hou; Min-Ying Lin; Yu-Chuan Lin; Hui-Yen Chuang; Yi-Jang Lee (Journal of Medical and Biological Engineering, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Development of novel polymorphic microsatellite markers for Picea brachytyla - Shuai-Peng Si; Chun-Jing Wang; Ji-Zhong Wan; Yu-Lin Qian; Chun-Hui Zhang (Molecular Biology Reports, 2022)

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

The management of bone defect using long non-coding RNA as a potential biomarker for regulating the osteogenic differentiation process - Jia-lin Liu; Yan-shi Liu; Mei-jie Zheng; Hui-yu He (Molecular Biology Reports, 2022)
Tissue engineered bone brings hope to the treatment of bone defects, and the osteogenic differentiation of stem cells is the key link. Inducing osteogenic differentiation of stem cells may be a potential approach to promote bone regeneration. In recent years, lncRNA has been studied in the field increasingly, which is believed can regulate cell cycle, proliferation, metastasis, differentiation and immunity, participating in a variety of physiology and pathology processes. At present, it has been confirmed that certain lncRNAs regulate the osteogenesis of stem cells and take part in mediating signaling pathways including Wnt/β-catenin, MAPK, TGF-β/BMP, and Notch pathways. Here, we provided an overview of lncRNA, reviewed its researches in the osteogenic differentiation of stem cells, emphasized the importance of lncRNA in bone regeneration, and focused on the roles of lncRNA in signaling pathways, in order to make adequate preparations for applying lncRNA to bone tissue Engineering, letting it regulate the osteogenic differentiation of stem cells for bone regeneration.

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Characterization of alkaloids in radix Sophora tonkinensis by UPLC-Q-TOF-MS/MS and its application in the comparison of two different habitats - Xing-Xing Zong; Yu Wang; Jia-Liang Xiong; Yu-Hui Ping; Qiong-Lin Liang (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Regulatory role of miR-129 and miR-384-5p on apoptosis induced by oxygen and glucose deprivation in PC12 cell - Hui-Lin Guan; Yue Guan; Wen-Yuan Li; Jia-Wei Liu; Yu-Jia Zheng; Yan-Zhong Guan; Hong-Feng Liu; Li-Xin Guan; Feng-Guo Zhai (Experimental Brain Research, 2022)

210Po-210Pb Disequilibrium in the Western North Pacific Ocean: Particle Cycling and POC Export - Qiangqiang Zhong; Tao Yu; Hui Lin; Jing Lin; Jianda Ji; Jialin Ni; Jinzhou Du; Dekun Huang (Frontiers in Marine Science, 2021)
Estimating the particulate organic carbon (POC) export flux from the upper ocean is fundamental for understanding the efficiency of the biological carbon pump driven by sinking particles in the oceans. The downward POC flux from the surface ocean based on 210 Po- 210 Pb disequilibria in seawater samples from the western North Pacific Ocean (w-NPO) was measured in the early summer (May-June) of 2018. All the profiles showed a large 210 Po deficiency relative to 210 Pb in the euphotic zone (0–150 m), while this 210 Po deficiency vanished below ∼500 m (with 210 Po/ 210 Pb ∼1 or > 1). A one-dimensional steady-state irreversible scavenging model was used to quantify the scavenging and removal fluxes of 210 Po and 210 Pb in the euphotic zone of the w-NPO. In the upper ocean (0–150 m), dissolved 210 Po (D-Po) was scavenged into particles with a residence time of 0.6–5.5 year, and the 210 Po export flux out of the euphotic zone was estimated as (0.33–3.49) × 10 4 dpm/m 2 /year, resulting in a wide range of particulate 210 Po (P-Po) residence times (83–921 days). However, in the deep ocean (150–1,000 m), 210 Po was transferred from the particulate phase to the dissolved phase. Using an integrated POC inventory and the P-Po residence times (Eppley model) in the w-NPO euphotic zone, the POC export fluxes (mmol C/m 2 /d) varied from 0.6 ± 0.2 to 8.8 ± 0.4. In comparison, applying the POC/ 210 Po ratio of all (>0.45 μm) particles to 210 Po export flux (Buesseler model), the obtained POC export fluxes (mmol C/m 2 /d) ranged from 0.7 ± 0.1 to 8.6 ± 0.8. Both Buesseler and Eppley methods showed enhanced POC export fluxes at stations near the continental shelf (i.e., Luzon Strait and the Oyashio-Kuroshio mixing region). The Eppley model-based 210 Po-derived POC fluxes agreed well with the Buesseler model-based fluxes, indicating that both models are suitable for assessing POC fluxes in the w-NPO. The POC export efficiency was < 15%, suggesting a moderate biological carbon pump efficiency in the w-NPO. These low export efficiencies may be associated with the dominance of smaller particles and the processes of degradation and subsequent remineralization of these small particles in the euphotic zone of oligotrophic regions in the w-NPO.

Dinoflagellate-targeted PCR reveals highly abundant and diverse communities of parasitic dinoflagellates in and near Zhubi Reef, South China Sea - Dajun Qiu; Liangmin Huang; Yunyun Zhuang; Yu Zhong; Yuehui Tan; Xiubao Li; Sheng Liu; Hui Huang; Senjie Lin (Coral Reefs, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

Empathy-based tolerance towards poor norm violators in third-party punishment - Hui Ouyang; Jingqian Yu; Jipeng Duan; Li Zheng; Lin Li; Xiuyan Guo (Experimental Brain Research, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Roles of bulk and rhizosphere denitrifying bacteria in denitrification from paddy soils under straw return condition - Ning Wang; Ya-Hui Zhao; Jian-Guang Yu; Li-Hong Xue; Hong-Bo Li; Lin-Zhang Yang (Journal of Soils and Sediments, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Identification and characterization of CONSTANS-like genes from Curcuma alismatifolia - Yuan-Yuan Li; Xiao-Huang Chen; Hui-Wen Yu; Qi-Lin Tian; Luan-Mei Lu (Horticulture, Environment, and Biotechnology, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Environmental Effects on the Spatiotemporal Variability of Fish Larvae in the Western Guangdong Waters, China - Yuting Feng; Lijun Yao; Hui Zhao; Jing Yu; Zhaojin Lin (Journal of Marine Science and Engineering, 2021)
Spawning grounds occupy an important position in the survival and reproduction of aquatic life, which plays an important role in the replenishment of fishery resources, especially in the China coasts where fishery resources are depleting. This study investigated environmental effects on the spatiotemporal variability of fish larvae in the western Guangdong waters (WGWs), on the basis of generalized additive models (GAMs) and center of gravity (CoG). Satellite data including sea surface salinity (SSS), sea surface temperature (SST), and in situ observations for fish larvae from April to June in 2014–2015 were used. Results showed that 40.3% of the total variation in fish larvae density was explained. SST, SSS, and depth showed positive effects in 23–24 °C and 27–30 °C, 24–32 PSU, and 0–60 m, and showed negative effects in 24–27 °C, 32–34.2 PSU, 60–80 m. Based on the stepwise GAMs, the most important factor was month, with a contribution of 10.6%, followed by longitude, offshore distance, depth, and latitude, with contributions of 7.0%, 7.0%, 6.3%, 4.2%, 3.9%, and 1.3%, respectively. Fish larvae CoG shifted northward by 0.6° N and eastwards by 0.13° E from April to June. The distribution of fish larvae in the WGWs was affected by complex submarine topography in the Qiongzhou Strait, coastal upwelling in the WGWs, and runoff from the Pearl River.

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Projections from Infralimbic Cortex to Paraventricular Thalamus Mediate Fear Extinction Retrieval - Yan Tao; Cheng-Yun Cai; Jia-Yun Xian; Xiao-Lin Kou; Yu-Hui Lin; Cheng Qin; Hai-Yin Wu; Lei Chang; Chun-Xia Luo; Dong-Ya Zhu (Neuroscience Bulletin, 2021)

Influences of organic material application on the physically separated soil organic carbon and nitrogen fractions in rice fields - Qiaogang Yu; Jing Ye; Wanchun Sun; Hui Lin; Qiang Wang; Junwei Ma (Journal of Soils and Sediments, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

WDR5a functions in cadmium-inhibited root meristem growth by regulating nitric oxide accumulation in Arabidopsis - Yu Zhang; Yang-Yang Tian; Lin-Feng Wang; Yun-Hui Li; Ting-Ting Li; Wen-Cheng Liu (Planta, 2020)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Two new species of Hortiboletus (Boletaceae, Boletales) from China - Hui-Jing Xie; Wen-Fei Lin; Shuai Jiang; Rou Xue; Lu-Ling Wu; Yu-Zhuo Zhang; Zhi-Qun Liang; Nian-Kai Zeng; Ming-Sheng Su (Mycological Progress, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Evaluation of the production-living-ecology space function suitability of Pingshan County in the Taihang mountainous area, China - Shu-hui Yu; Wei Deng; You-xin Xu; Xia Zhang; Hao-lin Xiang (Journal of Mountain Science, 2020)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

Association Between PSD95 Gene 3′UTR Single Nucleotide Polymorphism and Risk of Acute Ischemic Stroke in Chinese Han Population - Ying-Ying Lin; Tong-ya Yu; Hui Quan; Yu-Juan Chen; Xue-Yuan Liu; Dong-Ya Huang (Journal of Molecular Neuroscience, 2020)

Nitrogen and phosphorus co-starvation inhibits anthocyanin synthesis in the callus of grape berry skin - Hui-Zhen Zheng; Huan Wei; Shui-Huan Guo; Xin Yang; Ming-Xin Feng; Xu-Qiao Jin; Yu-Lin Fang; Zhen-Wen Zhang; Teng-Fei Xu; Jiang-Fei Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Correction to: Computer vision–based sensors for the tilt monitoring of an underground structure in a landslide area - I-Hui Chen; Yu-Shu Lin; Miau-Bin Su (Landslides, 2020)

Computer vision–based sensors for the tilt monitoring of an underground structure in a landslide area - I-Hui Chen; Yu-Shu Lin; Miau-Bin Su (Landslides, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Gallic Acid Attenuated LPS-Induced Neuroinflammation: Protein Aggregation and Necroptosis - Yu-Ling Liu; Chia-Chi Hsu; Hui-Ju Huang; Chih-Jung Chang; Shu-Hui Sun; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

Seroprevalence of porcine bocavirus in pigs in north-central China using a recombinant-NP1-protein-based indirect ELISA - Qian-Kai Shi; Jian-Lou Zhang; Wen-Yuan Gu; Lin-Shan Hou; Guang-Fu Yuan; Shao-Jie Chen; Jing-Hui Fan; Yu-Zhu Zuo (Archives of Virology, 2019)

Different intensity of autophagy regulate interleukin-33 to control the uncontrolled inflammation of acute lung injury - Ming Lei; Chuan-jiang Wang; Feng Yu; Ke Xie; Shi-hui Lin; Fang Xu (Inflammation Research, 2019)

Slope deformation monitoring in the Jiufenershan landslide using time domain reflectometry technology - Shei-Chen Ho; I-Hui Chen; Yu-Shu Lin; Jun-Yang Chen; Miau-Bin Su (Landslides, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Spatial and temporal evolution of landfast ice near Zhongshan Station, East Antarctica, over an annual cycle in 2011/2012 - Jiechen Zhao; Qinghua Yang; Bin Cheng; Matti Leppäranta; Fengming Hui; Surui Xie; Meng Chen; Yining Yu; Zhongxiang Tian; Ming Li; Lin Zhang (Acta Oceanologica Sinica, 2019)

Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China - Xun Yu; Gang Zeng; Li-Hui Chen; Sen-Lin Hu; Zhi-Qiang Yu (International Geology Review, 2019)

Effect of Partial Root-Zone Drying Irrigation (PRD) on the Gas Exchange and Antioxidant Enzymatic Activities in Alfalfa - Jing Zhang; Hui Xia Liu; Xiao Pan Pang; Cheng Yu; Qian Wang; Yu Pei Zhou; Li Guo Lin; Zheng Gang Guo (Journal of Soil Science and Plant Nutrition, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Spatiotemporal crop NDVI responses to climatic factors in mainland China - Hongshuo Wang; Xiaoxuan Liu; Xiaodong Zhang; Pengxin Wang; Hui Lin; Le Yu (International Journal of Remote Sensing, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Clearance of Amyloid Beta and Tau in Alzheimer’s Disease: from Mechanisms to Therapy - Shu-Hui Xin; Lin Tan; Xipeng Cao; Jin-Tai Yu; Lan Tan (Neurotoxicity Research, 2018)

Deformation process and mechanism analyses for a planar sliding in the Mayanpo massive bedding rock slope at the Xiangjiaba Hydropower Station - Shi-lin Zhang; Zhao-hui Zhu; Shun-chao Qi; Yu-xiang Hu; Qing Du; Jia-wen Zhou (Landslides, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

Brittleness characteristics of tight oil siltstones - Wen-Hui Tan; Jing Ba; Meng-Qiu Guo; Hui Li; Lin Zhang; Ting Yu; Hao Chen (Applied Geophysics, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Increased temperature mitigates the effects of ocean acidification on the calcification of juvenile Pocillopora damicornis, but at a cost - Lei Jiang; Fang Zhang; Ming-Lan Guo; Ya-Juan Guo; Yu-Yang Zhang; Guo-Wei Zhou; Lin Cai; Jian-Sheng Lian; Pei-Yuan Qian; Hui Huang (Coral Reefs, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Neuroprotective Effects of Baicalein on Acrolein-induced Neurotoxicity in the Nigrostriatal Dopaminergic System of Rat Brain - Wei-Zhong Zhao; Hsiang-Tsui Wang; Hui-Ju Huang; Yu-Li Lo; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Effects of prenatal caffeine exposure on glucose homeostasis of adult offspring rats - Hao Kou; Gui-hua Wang; Lin-guo Pei; Li Zhang; Chai Shi; Yu Guo; Dong-fang Wu; Hui Wang (The Science of Nature, 2017)

Association of MSI2 Gene Polymorphism with Age-at-Onset of Schizophrenia in a Chinese Population - Zhi-Lin Luan; Xiao-Hui Cui; Hu Xu; He-Yuan Lu; Yu-Yuan Li; Tian-Lan Lu; Dai Zhang (Neuroscience Bulletin, 2017)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

Targeted lipidomics profiling of acute arsenic exposure in mice serum by on-line solid-phase extraction stable-isotope dilution liquid chromatography–tandem mass spectrometry - Chao-Yu Chen; Pinpin Lin; Ming-Hsien Tsai; Hui-Ling Lee (Archives of Toxicology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

Retraction Note to: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly(ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Grape hexokinases are involved in the expression regulation of sucrose synthase- and cell wall invertase-encoding genes by glucose and ABA - Xiu-Qin Wang; Li-Li Zheng; Hao Lin; Fei Yu; Li-Hui Sun; Li-Mei Li (Plant Molecular Biology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Influences of Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on Heavy Metals and Inorganic Nitrogen Transformation in the Rice Field Surface Water - Qiaogang Yu; Junwei Ma; Wanchun Sun; Hui Lin; Qiang Wang; Jianrong Fu (Water, Air, & Soil Pollution, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Modeling and Manufacturing Technology for Personalized Biological Fixed Implants - Zhang Guoqing; Yang Yongqiang; Lin Hui; Song Changhui; Xiao Ran; Yu Jiakuo (Journal of Medical and Biological Engineering, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Plasma Amyloid-Beta Levels in Patients with Different Types of Cancer - Wang-Sheng Jin; Xian-Le Bu; Yu-Hui Liu; Lin-Lin Shen; Zhen-Qian Zhuang; Shu-Sheng Jiao; Chi Zhu; Qing-Hua Wang; Hua-Dong Zhou; Tao Zhang; Yan-Jiang Wang (Neurotoxicity Research, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

RETRACTED ARTICLE: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly (ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Diagnosing the possible dynamics controlling Sahel precipitation in the short-range ensemble community atmospheric model hindcasts - Yu-heng Tseng; Yen-heng Lin; Min-hui Lo; Shu-chih Yang (Climate Dynamics, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Two AMT2-Type Ammonium Transporters from Pyrus betulaefolia Demonstrate Distinct Expression Characteristics - Hui Li; Yu Cong; You-hong Chang; Jing Lin (Plant Molecular Biology Reporter, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Controversial opinion: evaluation of EGR1 and LAMA2 loci for high myopia in Chinese populations - Fang-yu Lin; Zhu Huang; Ning Lu; Wei Chen; Hui Fang; Wei Han (Journal of Zhejiang University-SCIENCE B, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Data Perturbation Method Based on Contrast Mapping for Reversible Privacy-preserving Data Mining - Yuan-Hung Kao; Wei-Bin Lee; Tien-Yu Hsu; Chen-Yi Lin; Hui-Fang Tsai; Tung-Shou Chen (Journal of Medical and Biological Engineering, 2015)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers therapy and colorectal cancer: a systematic review and meta-analysis - Yi-Ning Dai; Jing-Hua Wang; Jin-Zhou Zhu; Jie-Qiong Lin; Chao-Hui Yu; You-Ming Li (Cancer Causes & Control, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Generation by reverse genetics of an effective attenuated Newcastle disease virus vaccine based on a prevalent highly virulent Chinese strain - Meng-Meng Liu; Jin-Long Cheng; Xiao-Hui Yu; Zhuo-Ming Qin; Fu-Lin Tian; Guo-Zhong Zhang (Biotechnology Letters, 2015)

Transcriptome-wide identification of the genes responding to replanting disease in Rehmannia glutinosa L. roots - Yan Hui Yang; Ming Jie Li; Xin Yu Li; Xin Jian Chen; Wen Xiong Lin; Zhong Yi Zhang (Molecular Biology Reports, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Temperature‐sensitive fitness cost of insecticide resistance in C hinese populations of the diamondback moth P lutella xylostella - Lin Jie Zhang; Yu Pu Jing; Xiao Hui Li; Chang Wei Li; Denis Bourguet; Gang Wu (Molecular Ecology, 2015)
Alleles conferring a higher adaptive value in one environment may have a detrimental impact on fitness in another environment. Alleles conferring resistance to pesticides and drugs provide textbook examples of this trade‐off as, in addition to conferring resistance to these molecules, they frequently decrease fitness in pesticide/drug‐free environments. We show here that resistance to chlorpyrifos, an organophosphate ( OP ), in Chinese populations of the diamondback moth, Plutella xylostella , is conferred by two mutations of ace1 – the gene encoding the acetylcholinesterase enzyme targeted by OP s – affecting the amino acid sequence of the corresponding protein. These mutations were always linked, consistent with the segregation of a single resistance allele, ace1R , carrying both mutations, in the populations studied. We monitored the frequency of ace1R (by genotyping more than 20 000 adults) and the level of resistance (through bioassays on more than 50 000 individuals) over several generations. We found that the ace1R resistance allele was costly in the absence of insecticide and that this cost was likely recessive. This fitness costs involved a decrease in fecundity: females from resistant strains laid 20% fewer eggs, on average, than females from susceptible strains. Finally, we found that the fitness costs associated with the ace1R allele were greater at high temperatures. At least two life history traits were involved: longevity and fecundity. The relative longevity of resistant individuals was affected only at high temperatures and the relative fecundity of resistant females – which was already affected at temperatures optimal for development – decreased further at high temperatures. The implications of these findings for resistance management are discussed.

Energy balance-based SWAT model to simulate the mountain snowmelt and runoff — taking the application in Juntanghu watershed (China) as an example - Xian-Yong Meng; Dan-Lin Yu; Zhi-Hui Liu (Journal of Mountain Science, 2015)

Development of microsatellite markers in the rice paddy snake Enhydris plumbea (Colubridae) - Yu Du; Xiao-Xiao Zheng; Yun-Tao Yao; Long-Hui Lin (Conservation Genetics Resources, 2015)

Molecular cloning and identification of an ammonium transporter gene from pear - Hui Li; Yu Cong; Jing Lin; You Hong Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Calcitonin Gene-Related Peptide Inhibits Osteolytic Factors Induced by Osteoblast In Co-Culture System with Breast Cancer - Hui Zhao; Lin-lin Ning; Zhi-yu Wang; Hong-tao Li; Dan Qiao; Yang Yao; Huan-long Qin (Cell Biochemistry and Biophysics, 2014)

Kinetics of nitrification in a fixed biofilm reactor using dewatered sludge-fly ash composite ceramic particle as a supporting medium - Mong-Chuan Lee; Yen-Hui Lin; Huang-Wei Yu (Biodegradation, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Neuronal and Astroglial TGFβ-Smad3 Signaling Pathways Differentially Regulate Dendrite Growth and Synaptogenesis - Chuan-Yong Yu; Wei Gui; Hui-Yan He; Xiao-Shan Wang; Jian Zuo; Lin Huang; Nong Zhou; Kai Wang; Yu Wang (NeuroMolecular Medicine, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Variants of COL3A1 Are Associated with the Risk of Stroke Recurrence and Prognosis in the Chinese Population: a Prospective Study - Wenfei Lv; Yahui Lin; Weihua Song; Kai Sun; Hui Yu; Yinhui Zhang; Channa Zhang; Liang Li; Miaomiao Suo; Rutai Hui; Jingzhou Chen (Journal of Molecular Neuroscience, 2014)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

Development of microsatellite markers in the gray ratsnake Ptyas korros (Colubridae) - Xiao-Xiao Zheng; Yu Du; Long-Hui Lin; Chi-Xian Lin (Conservation Genetics Resources, 2014)

Development of microsatellite markers in the beauty rat snake Elaphe taeniura (Colubridae) - Xiao-Xiao Zheng; Yu Du; Long-Hui Lin; Chi-Xian Lin (Conservation Genetics Resources, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Mapping Soil Particle Size Fractions Using Compositional Kriging, Cokriging and Additive Log-ratio Cokriging in Two Case Studies - Xiao-Lin Sun; Yun-Jin Wu; Hui-Li Wang; Yu-Guo Zhao; Gan-Lin Zhang (Mathematical Geosciences, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Three new polyketides from marine-derived fungus Penicillium citrinum SCSGAF 0167 - Yu-Lin Sun; Xiao-Yong Zhang; Zhi-Hui Zheng; Xin-Ya Xu; Shu-Hua Qi (Natural Product Research, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

CarNAC2, a novel NAC transcription factor in chickpea (Cicer arietinum L.), is associated with drought-response and various developmental processes in transgenic arabidopsis - Xingwang Yu; Hui Peng; Yanmin Liu; Yan Zhang; Yingjie Shu; Quanjia Chen; Shubing Shi; Lin Ma; Hao Ma; Hua Zhang (Journal of Plant Biology, 2014)

Toxic effects of hexaflumuron on the development of Coccinella septempunctata - Caihong Yu; Maoran Fu; Ronghua Lin; Yan Zhang; Liu Yongquan; Hui Jiang; Theo C. M. Brock (Environmental Science and Pollution Research, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

TGFβ1 Treatment Reduces Hippocampal Damage, Spontaneous Recurrent Seizures, and Learning Memory Deficits in Pilocarpine-Treated Rats - Liang-Yong Li; Jia-Lin Li; Hui-Min Zhang; Wen-Ming Yang; Kai Wang; Yuan Fang; Yu Wang (Journal of Molecular Neuroscience, 2013)

Effectiveness of participatory training for prevention of musculoskeletal disorders: a randomized controlled trial - Wenzhou Yu; Ignatius T. S. Yu; Xiaorong Wang; Zhimin Li; Sabrina Wan; Hong Qiu; Hui Lin; Shaohua Xie; Trevor Sun (International Archives of Occupational and Environmental Health, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Adsorption with biodegradation for decolorization of reactive black 5 by Funalia trogii 200800 on a fly ash-chitosan medium in a fluidized bed bioreactor-kinetic model and reactor performance - Yen-Hui Lin; Wen-Fan Lin; Kai-Ning Jhang; Pei-Yu Lin; Mong-Chuan Lee (Biodegradation, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Combining proteomics, serum biomarkers and bioinformatics to discriminate between esophageal squamous cell carcinoma and pre-cancerous lesion - Xiao-hui Zhai; Jie-kai Yu; Chen Lin; Li-dong Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Chemoselective synthesis, antiproliferative activities, and SAR study of 1H-pyrazol-5-yl-N,N-dimethylformamidines and pyrazolyl-2-azadienes - Kau-Shan Wen; Hui-Yi Lin; Yu-Ying Huang; Kimiyoshi Kaneko; Hiroyuki Takayama; Masayuki Kimura; Shin-Hun Juang; Fung Fuh Wong (Medicinal Chemistry Research, 2012)

First record of wild ephyrae of the giant jellyfish Nemopilema nomurai - Masaya Toyokawa; Masashi Shibata; Jia-Hua Cheng; Hui-Yu Li; Jian-Zhong Ling; Nan Lin; Zun-Lei Liu; Yi Zhang; Manabu Shimizu; Hideki Akiyama (Fisheries Science, 2012)

Dorsal root ganglion compression as an animal model of sciatica and low back pain - Xiao-Yu Lin; Jing Yang; Hui-Ming Li; San-Jue Hu; Jun-Ling Xing (Neuroscience Bulletin, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of isoflurane exposure during pregnancy on postnatal memory and learning in offspring rats - Fei-juan Kong; Yu-wen Tang; Ai-fei Lou; Hong Chen; Lin-hao Xu; Xiao-ming Zhang; Hui-shun Lu (Molecular Biology Reports, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Analysis of the expression of BohLOL1, which encodes an LSD1-like zinc finger protein in Bambusa oldhamii - Sheng-Hsiung Yeh; Choun-Sea Lin; Fu-Hui Wu; Ai-Yu Wang (Planta, 2011)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

A new alkaloid from the marine-derived fungus Hypocrea virens - Tao Liu; Zhan-Lin Li; Yu Wang; Li Tian; Yue-Hu Pei; Hui-Ming Hua (Natural Product Research, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Phylogeographic heterogeneity of the brown macroalga Sargassum horneri (Fucaceae) in the northwestern Pacific in relation to late Pleistocene glaciation and tectonic configurations - ZI‐MIN HU; SHINYA UWAI; SHEN‐HUI YU; TERUHISA KOMATSU; TETSURO AJISAKA; DE‐LIN DUAN (Molecular Ecology, 2011)
Pleistocene glacial oscillations and associated tectonic processes are believed to have influenced the historical abundances and distribution of organisms in the Asia Northwest Pacific (ANP). Accumulating evidence indicates that factors shaping tempospatial population dynamics and distribution patterns of marine taxa vary with biogeographical latitude, pelagic behaviour and oceanographic regimes. To detect what kinds of historical and contemporary factors affected genetic connectivity, phylogeographic profiles of littoral macroalga Sargassum horneri in the ANP were analysed based on mitochondrial (Cox3) and chloroplast ( rbc L) data sets. Five distinct clades were recovered. A strong signature of biogeographical structure was revealed (Φ CT = 0.487, P 0.0001) derived from remarkable differentiation in clade distribution, as clade I is restricted to Chinese marginal seas (Yellow–Bohai Sea, East China Sea and South China Sea), whereas clades II–V are discontinuously scattered around the main Islands of Japan. Furthermore, two secondary contact regions were identified along the south Japan‐Pacific coastline. This significant differentiation between the two basins may reflect historical glacial isolation in the northwestern Pacific, which is congruent with the estimates of clade divergence and demographic expansion during the late Quaternary low sea levels. Analysis of molecular variance and the population‐pair statistic F ST also revealed significant genetic structural differences between Chinese marginal seas and the Japanese basin. This exceptional phylogeographic architecture in S. horneri , initially shaped by historical geographic isolation during the late Pleistocene ice age and physical biogeographical barriers, can be complicated by oceanographic regimes (ocean surface currents) and relocating behaviour such as oceanic drifting.

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Electrostatic droplets assisted synthesis of alginate microcapsules - Keng-Shiang Huang; Chih-Hui Yang; Yung-Sheng Lin; Chih-Yu Wang; Kang Lu; Yu-Fan Chang; Yi-Ling Wang (Drug Delivery and Translational Research, 2011)

A method of urban ecological risk assessment: combining the multimedia fugacity model and GIS - Hui Min Song; Lin Yu Xu (Stochastic Environmental Research and Risk Assessment, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Role of Lys281 in the Dunaliella salina (6-4) Photolyase Reaction - Feiwei Zhang; Hui Xu; Yu Cao; Tao Wen; Jiafu Lin; Gen Ma; Dairong Qiao; Yi Cao (Current Microbiology, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Responses of soil chemical and biological properties to nitrogen addition in a Dahurian larch plantation in Northeast China - Ya-Lin Hu; De-Hui Zeng; Yun-Xia Liu; Yu-Lan Zhang; Zhen-Hua Chen; Zheng-Quan Wang (Plant and Soil, 2010)

Wound repair and anti-oxidative capacity is regulated by ITGB4 in airway epithelial cells - Chi Liu; Hui-jun Liu; Yang Xiang; Yu-rong Tan; Xiao-lin Zhu; Xiao-qun Qin (Molecular and Cellular Biochemistry, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Degradation of phenanthrene by the endophytic fungus Ceratobasidum stevensii found in Bischofia polycarpa - Chuan-chao Dai; Lin-shuang Tian; Yu-ting Zhao; Yan Chen; Hui Xie (Biodegradation, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Influence of N-Terminal Truncations on the Functional Expression of Bacillus licheniformis γ-Glutamyltranspeptidase in Recombinant Escherichia coli - Long-Liu Lin; Li-Yu Yang; Hui-Yu Hu; Huei-Fen Lo (Current Microbiology, 2008)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

GTPase activity is not essential for the interferon-inducible MxA protein to inhibit the replication of hepatitis B virus - Zhijian Yu; Zhanhui Wang; Jinjun Chen; Hui Li; Zhanzhou Lin; Fan Zhang; Yuanping Zhou; Jinlin Hou (Archives of Virology, 2008)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Identification of a Kunitz inhibitor from Albizzia kalkora and its inhibitory effect against pest midgut proteases - Jia-Yu Zhou; Hai Liao; Nian-Hui Zhang; Lin Tang; Ying Xu; Fang Chen (Biotechnology Letters, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Basic Characteristics of Sporolactobacillus inulinus BCRC 14647 for Potential Probiotic Properties - Hui-Ying Huang; Shih-Yi Huang; Pei-Yu Chen; V. An-Erl King; Yeu-Pyng Lin; Jen-Horng Tsen (Current Microbiology, 2007)

The functional haplotype of peptidylarginine deiminase IV (S55G, A82V and A112G) associated with susceptibility to rheumatoid arthritis dominates apoptosis of acute T leukemia Jurkat cells - Hui-Chih Hung; Chien-Yu Lin; Ya-Fan Liao; Pei-Chen Hsu; Gregory J. Tsay; Guang-Yaw Liu (Apoptosis, 2007)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

Phylogenetic Analysis and Biochemical Characterization of a Thermostable Dihydropyrimidinase from Alkaliphilic Bacillus sp. TS-23 - Long-Liu Lin; Wen-Hwei Hsu; Wei-Yi Hsu; Shu-Chen Kan; Hui-Yu Hu (Antonie van Leeuwenhoek, 2005)

Changes in Soil Properties After Establishment of Artemisia halodendron and Caragana microphylla on Shifting Sand Dunes in Semiarid Horqin Sandy Land, Northern China - Yong Zhong Su; Tong Hui Zhang; Yu Lin Li; Fang Wang (Environmental Management, 2005)

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Intracellular expression of Vitreoscilla hemoglobin in Aspergillus terreus to alleviate the effect of a short break in aeration during culture - Yu-Hui Lin; Ywan-Feng Li; Min-Chang Huang; Ying-Chieh Tsai (Biotechnology Letters, 2004)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Stopped-flow kinetic study of the peroxidase reactions of mangano-microperoxidase-8 - Hui-Chun Yeh; Chia-Huei Yu; Jinn-Shyan Wang; Suei-Tein Chen; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)